EFFECT OF TRANSFER OF TRAINING IN INCREASING ORGANIZATIONAL PRODUCTIVITY - Shah Bukhari, Noor; Ali Junejo, Mumtaz; Ali Soomro, Farhan; Hussain Sahito, Zahid (International Journal of Psychosocial Rehabilitation, 2020)
The training is essential for a competent and effective workforce. Employees’ training and development is the method to transfer expertise and knowledge among employees at the organizational level. Training of employees is a basic concern for management to sustain in challenging environments. Nowadays, firms are doing their best in employee training because they understand the importance of training. Sometimes, training transfer among employees is inadequate because of differences in the workplace and training environment. This study aims to gain insight into some of the factors that determine the transfer of training to the work context. The focus of this research is to indicate the relationship among transfer of training and organizational effectiveness in the context of Shah Abdul Latif University (Khairpur, Pakistan). Our findings have also supported the assumption that employees from Shah Abdul Latif University Khairpur need training because training will serve as a path that would lead them towards better and improved productivity. This research indicates the importance of training in employees, like the backbone of firms, and suggests firms should focus on training to get organizational outcomes effectively and different strategic plans to overcome the problems at the time of transferring from training to the work environment.